A new species of Zonana DeLong & Freytag (Hemiptera: Cicadellidae: Iassinae: Gyponini) from Peru with a key to species of the genus - Magalhães, Raysa Brito De; Gonçalves, Clayton Corrêa; Takiya, Daniela Maeda (Zootaxa, 2014)
A new species of the genus Zonana DeLong & Freytag, 1963 from Peru is described and illustrated: Z. petalacea sp. nov. This species is easily distinguished from other species of the genus by its peculiar aedeagus with a pair of slender ventral processes and a unique flattened petal-shaped dorsal process. A taxonomic key to the now four known species of Zonana is provided.